ҚАЗАҚСТАН РЕСПУБЛИКАСЫ БАНК ЖҮЙЕСІНДЕГІ ЕКІНШІ ДЕҢГЕЙДЕГІ БАНКТЕРДІҢ ҚҰҚЫҚТЫҚ ЖАҒДАЙЫ (Journal of actual problems of jurisprudence, 2019)
The article reviews the legal position of banks in the Republic of Kazakhstan. The article expresses the view that banks whichimportant role for the economy of country.